Vocabulary Learning Strategies Through Short Stories - Nayak, Tushar (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The study envisages the use of short stories to enrich the vocabulary acquisition of elementary school students through the deployment of strategies with the help of dictionaries. The study aims to improve the vocabulary acquisition of elementary school students by suggesting suitable materials appropriate for their age, interest, and vicinity. Vocabulary learning strategies with the help of dictionaries have significantly influenced vocabulary acquisition in elementary school students. Thus, the study utilizes dictionary learning strategies from